Posterior cranial FOSSA space occupying lesions: an institutional experience - Meenakshisundaram, Natarajan; Dhandapani, Balasubramanian (International Journal of Research in Medical Sciences, 2018)
Background: Tumors in the Posterior fossa are well known for their critical location and complications as they result in brain stem compression and hydrocephalus. This study was conducted to analyze the histological types, frequency and prognosis of the posterior cranial fossa tumors in children and adults at Institute of Neurosurgery, Madras Medical College, Chennai, Tamilnadu. Methods: It was a descriptive study in which 108 consecutive cases of posterior cranial fossa tumors in children and adults were studied from December 2016 to November 2017. During this period, patients with posterior cranial fossa tumors were thoroughly studied and analysed regarding further management options. Results: Out of 108 cases in our study, 60 (56%) cases were male and 48 (44%) were female patients. The morphological distribution of the posterior cranial fossa tumors was as follows: schwannoma 36 (33%) cases, meningioma 24 (22%) cases, medulloblastoma 14 (13%) cases, pilocytic astrocytoma 17(16%) cases, high grade astrocytoma 7 (7%) cases, metastasis 8 (8%) cases, round blue cell tumor 2 (2%) cases. Conclusions: Brainstem compression, herniation, and death are all risks in tumors which occur in this critical location. Tumors in the posterior fossa are considered critical brain lesions, primarily because of the limited space within the posterior fossa and the potential involvement of vital brain stem nuclei.